Traffic-related air pollution in relation to respiratory symptoms, allergic sensitisation and lung function in schoolchildren. Issue 7 (13th October 2008) - Rosenlund, M; Forastiere, F; Porta, D; De Sario, M; Badaloni, C; Perucci, C A
Abstract : Background: Urban air pollution can trigger asthma exacerbations, but the effects of long-term exposure to traffic-related air pollution on lung function or onset of airway disease and allergic sensitisation in children is less clear. Methods: All 2107 children aged 9–14 years from 40 schools in Rome in 2000–1 were included in a cross-sectional survey. Respiratory symptoms were assessed on 1760 children by parental questionnaires (response rate 83.5%). Allergic sensitisation was measured by skin prick tests and lung function was measured by spirometry on 1359 children (77.2%). Three indicators of traffic-related air pollution exposure were assessed: self-reported heavy traffic outside the child's home; the measured distance between the child's home and busy roads; and the residential nitrogen dioxide (NO2 ) levels estimated by a land use regression model (R 2 = 0.69). Results: There was a strong association between estimated NO2 exposure per 10 μg/m 3 and lung function, especially expiratory flows, in linear regression models adjusted for age, gender, height and weight: −0.62% (95% CI −1.05 to −0.19) for forced expiratory volume in 1 s as a percentage of forced vital capacity, −62 ml/s (95% CI −102 to −21) for forced expiratory flow between 25% and 75% of forced vital capacity and −85 ml/s (95% CI −135 to −35) for peak expiratory flow. The other two exposure indicators showed similar but weaker associations. The associations appeared stronger in girls, older children, in children of high socioeconomic status and in those exposed to parental smoking. Although lifetime asthma was not an effect modifier, there was a suggestion of a larger effect on lung function in subjects with a positive prick test. Multiple logistic regression models did not suggest a consistent association between traffic-related air pollution exposure and prevalence of respiratory symptoms or allergic sensitisation. Conclusion: The results of this study suggest that residential traffic-related air pollution exposure is associated with reduced expiratory flows in schoolchildren.